Prediction of Pressure Drop with Pneumatic Conveying of Solids in Horizontal Pipes - Wirth, Karl-Ernst; Molerus, Otto (Preprints "Pneumatech I", 1982)
Current relationships for determination of the pressure drop with pneumatic conveying of solids in pipes are not of general validity. The theoretical considerations underlying these relationships do not take into account the influence of the rotatory motion of the particles. On the other hand, extremely high rotatory speeds of the particles due to wall collision are observed. Therefore a new concept is presented which takes into account the rotatory motion of the particles. A further aim was to represent the data in the form of nondimensional groups which allow meaningful, physical interpretation of the results obtained. A state diagram for the prediction of pressure drop with pneumatic conveying in the form of sliding particles strands is described. Calculation of power loss per particle and of the force and the moment acting on a particle leads to a nondimensional representation of pressure drop in which a normalized pressure drop is combined with a particle Froude number and a Froude number which contains the particle fall velocity and the pipe diameter. This combination of nondimensional groups defines fully suspended flow. The normalized pressure drop is defined in such a way that it represents the nondimensional slip of the particles, too. Comparison with pressure drop measurements for pneumatic transport in horizontal pipes which included changes in particle size, particles density and pipe diameter confirms the physical significance of the parameters used with regard to the prediction of pressure drop and of particles slip velocity. A simple procedure for the prediction of pressure drop in the full range of steady-state pneumatic conveying is proposed.
UnivIS-Import:2015-04-16:Pub.1982.tech.ITC.mechve.predic_71
Keywords: pressure; pneumatic; conveying